2011 49th Annual Allerton Conference on Communication, Control, and Computing (Allerton) 2011
DOI: 10.1109/allerton.2011.6120221
|View full text |Cite
|
Sign up to set email alerts
|

Congestion equilibrium for differentiated service classes

Abstract: In this paper, we introduce the notation of a congestion equilibrium where competing players share a common level of congestion in the system. We illustrate the concept by developing a framework under which content providers (CPs) compete for a last-mile bottleneck capacity of an ISP so as to service their users. We show that under minor monotonicity assumptions on the system congestion and traffic rates, a unique congestion equilibrium exists. Under an independence of scale assumption, we characterize the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…We have only found that Ma and Misra [22] considered the problem from similar directions with us. We adopt a similar methodology with Ma and Misra [22,27] to obtain the equilibrium of the Stackelberg game. However, we do not consider QoS differentiation, but we focus on the sponsored data plan.…”
Section: Related Workmentioning
confidence: 99%
“…We have only found that Ma and Misra [22] considered the problem from similar directions with us. We adopt a similar methodology with Ma and Misra [22,27] to obtain the equilibrium of the Stackelberg game. However, we do not consider QoS differentiation, but we focus on the sponsored data plan.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, CP i can take this throughput as given and estimate thatθ i = min{θ i , θ N }. The competitive equilibrium under the throughput-taking assumption can be regarded as a special type of congestion equilibrium [18], where the throughput of the CPs indicates the level of congestion in system.…”
Section: Competitive Equilibriummentioning
confidence: 99%
“…The above assumption implies that when the ISP scales its capacity µ linearly and smoothly with its consumer size M , the CPs will not diverge abruptly into another equilibrium, if there exists any. For the game (M, µ, N , s I ) with strategy 4 Please refer to [18] for evaluating a competitive equilibrium. Under the above assumption, the per capita consumer and ISP surplus will remain the same in linearly scaled games {(ξM, ξµ, N , s I ) : ξ > 0} in equilibrium.…”
Section: Competitive Equilibriummentioning
confidence: 99%